Wounding in the plant tissue: the defense of a dangerous passage - Savatin, Daniel V.; Gramegna, Giovanna; Modesti, Vanessa; Cervone, Felice (Frontiers in Plant Science, 2014)
Plants are continuously exposed to agents such as herbivores and environmental mechanical stresses that cause wounding and open the way to the invasion by microbial pathogens. Wounding provides nutrients to pathogens and facilitates their entry into the tissue and subsequent infection. Plants have evolved constitutive and induced defense mechanisms to properly respond to wounding and prevent infection. The constitutive defenses are represented by physical barriers, i.e., the presence of cuticle or lignin, or by metabolites that act as toxins or deterrents for herbivores. Plants are also able to sense the injured tissue as an altered self and induce responses similar to those activated by pathogen infection. Endogenous molecules released from wounded tissue may act as Damage-Associated Molecular Patterns (DAMPs) that activate the plant innate immunity. Wound-induced responses are both rapid, such as the oxidative burst and the expression of defense-related genes, and late, such as the callose deposition, the accumulation of proteinase inhibitors and of hydrolytic enzymes (i.e., chitinases and gluganases). Typical examples of DAMPs involved in the response to wounding are the peptide systemin, and the oligogalacturonides, which are oligosaccharides released from the pectic component of the cell wall. Responses to wounding take place both at the site of damage (local response) and systemically (systemic response) and are mediated by hormones such as jasmonic acid, ethylene, salicylic acid, and abscisic acid.